An illustrated brief history of western philosophy 20th anniversary edition - Kenny, Anthony 1931- (Wiley Blackwell, 2019)
Newly revised and expanded for a special 20th anniversary publication, the latest edition of An Illustrated Brief History of Western Philosophy contains all of Kenny's original writings on the history of Western philosophy from ancient to modern, along with new writings on the philosophy of the mid-20th century, covering important contributions from continental philosophers and philosophers of the post-Wittgenstein anglophone traditions including the work of many women who have too often been neglected by the historical record. - from bookjacket.